Mawas Diri dalam Upacara Api Abadi Khayangan Api ditinjau dari Perspektif Konseling Multibudaya - Naysilla Salsabila Umaroh; Rizqika Ghina Salsabila; Firsty Auwardani Kalimus; Fahma Ningrum Rahmasari (Jurnal Educazione : Jurnal Pendidikan, Pembelajaran dan Bimbingan dan konseling, 2026)
In the culture of the Javanese people, especially in Bojonegoro, the Khayangan Api Eternal Fire Ceremony contains philosophical values related to self-reflection, respect for ancestors, and social togetherness. These values can be a source of contextual learning in the development of cultural-based guidance and counseling services. This article aims to examine the relationship between the concept of self-reflection in the Eternal Fire Ceremony of Khayangan Api and the principles of multicultural counseling. This study uses a qualitative method with data collection techniques through interviews and relevant literature studies. The results of the study show that cultural values in the ceremony are relevant to the development of self-awareness through self-reflection, cultural identity awareness, and the meaning of individual life experiences. The integration of local cultural values in guidance and counseling services can be a source of contextual learning to help individuals identify with themselves, reflect on experiences, and strengthen cultural identity.